Criminalising the client: institutional change, gendered ideas, and feminist strategies - Erikson, Josefina (Feminist institutionalist perspectives, 2017)
Understanding the Swedish gender equality model - possibilities and limits -- Frame analysis as a new approach for studying feminist institutional change -- Tracing ideational changes concerning prostitution -- The 1992 battle of the committees as a critical juncture -- Proponents, resistance, and strategies